Peran Kepolisian Dalam Menanggulangi Tindak Pidana Judi Online (Studi Kasus Putusan Nomor 217/Pid.Sus/2025/PN.JKT.SEL) - Elthaufani, Lucky; Cumbrandika, Chitto (Neolectura, 2026)
The rapid growth of digital technology has intensified online gambling in Indonesia, posing complex challenges for law enforcement. This study analyzes the role of the Indonesian National Police (Polri) in handling online gambling crimes, focusing on the Komdigi employees case. Using a descriptive qualitative approach through literature review and policy analysis, the research examines the legal framework, enforcement practices, and obstacles faced by Polri. The findings show that Polri, through the Cyber Crime Directorate (Dittipidsiber) of Bareskrim, has carried out preventive measures such as public education and digital literacy campaigns, alongside repressive actions including digital forensic investigations, website blocking, and prosecution of offenders. The main challenges include ambiguous regulations in the ITE Law, cross-border jurisdictional issues, and limited inter-agency coordination. The study recommends more adaptive regulatory reforms, the use of artificial intelligence and big data for early detection, and stronger international cooperation to effectively combat transnational online gambling networks